Increasing the adoption of project management best practices in Jabatan Kerja Raya - Dahrawi Edrus, Sakinah (2015)
A good project management practices will save cost and improve the chances of completing the project on time or ahead of schedule. Poor project management in any project phases will contribute to delays, cost overrun and failure to perform the quality expectation by the customers. Tools and techniques for project management best practices such as systems, guidelines, manuals, templates and training modules had been developed by Jabatan Kerja Raya (JKR) and expected to be adopted by all the staff for the government project implementation. Hence, this paper presents a comprehensive study on the implementation of project management best practices in JKR projects. The aim of this study is to increase the adoption of project management best practices in JKR project implementation towards excellent project delivery and to achieve the following objectives; (1) identifying the acceptance level of project management best practices in JKR, (2) assessing the adoption rates of project management best practices in JKR and (3) establishing factors to increase adoption of project management best practices in JKR. A structured questionnaire was used as the main tool and distributed to various respondents from JKR staff which includes Head of Project Team (HOPT), Head of Design Team (HODT) and Superintendent Officer (SO) at multiple branches in JKR. From the 335 distributed surveys, 93 responses were collected. The findings showed that acceptance of project management best practices as a general are at the high level but the adoption rates are at the medium level. The top management support and commitment, good leadership of senior management and appointing a project consultant was ranked the top factors that will increase the adoption project management best practices in JKR project implementation, hence improving the project delivery system.